Analisa Tingkat Literasi Keuangan Syariah Dosen Dan Tenaga Kependidikan Perempuan Di Universitas Dharma Andalas - Fernanda, Dedi; Thahirah, Khadijah Ath; Wijaya, Riani Sukma (CV. ITTC INDONESIA, 2024)
This study aims to determine the level of Islamic Financial Literacy of lecturers and female education personnel at Dharma Andalas University. The Islamic financial literacy index includes the concept of money in Islam, Islamic banking, takaful and sharia-based investments. This study uses a quantitative descriptive method with data collection through questionnaires on lecturers and female education personnel at Dharma Andalas University. The level of Sharia Financial Literacy in female lecturers and education personnel at Dharma Andalas University needs to be done considering the important role of lecturers and education personnel in socializing public finance to the wider community. From the results of the study it can be concluded that the level of Sharia financial literacy (the concept of money, Sharia banks, takaful and Sharia investment) in lecturers and education personnel at Dharma Andalas University is very good. With a very good level of Sharia financial literacy, it is hoped that lecturers and education personnel can play an active role in educating and socializing about Sharia finance to the wider community.